VALIDACIÓN DE UN PROGRAMA ELECTRÓNICO PARA EL SEGUIMIENTO DE RECIÉN NACIDOS CON SÍFILIS CONGÉNITA - Samara Fernanda Vieira Valença; Camila Aparecida Pinheiro Landim Almeida; Jaqueline Carvalho Silva e Sales; Carmen Viana Ramos; Luana Kelle Batista Moura; Ellen Thallita Hill Araújo (Universidade Federal do Paraná, 2020)
Objective: To validate the content and appearance of an electronic tool for the monitoring of newborns with congenital syphilis. Method: Methodological study of validation of content and appearance. Data were collected from June to August 2018 with the use of assessment instruments for validation by seven medical specialists who teach at a higher education institution, with experience in pediatrics and/or infectious diseases, and who have completed their undergraduate courses more than 16 years ago. Content Validity Index with an established value of 0.78 was used. Results: Regarding structure and presentation, objectives and relevance, all items were considered validated by the experts. The global Content Validity Index was 0.97. Conclusion: The electronic tool was validated for content and appearance, and its contribution to nurses and doctors in primary care was the production of an easy-to-use tool for effective clinical monitoring of infants with congenital syphilis.